Variations of freezing tolerance and sugar concentrations of grape buds in response to foliar application of abscisic acid - Dami, Imed; Zhang, Yi (Frontiers in Plant Science, 2023)
The purpose of this study was to explore the mechanism of ABA-induced freezing tolerance increase in grapevines. The specific objectives were to evaluate the impact of ABA treatment on soluble sugar concentration in grape buds and determine the correlations between freezing tolerance and ABA-affected soluble sugar concentration. Vitis spp ‘Chambourcin’ and Vitis vinifera ‘Cabernet franc’ were treated with 400 and 600 mg/L ABA in the greenhouse and field. The freezing tolerance and soluble sugar concentration of grape buds were measured monthly during the dormant season in the field and at 2wk, 4wk, and 6wk after ABA application in the greenhouse. It was observed that fructose, glucose, and sucrose are the main soluble sugars that correlate with freezing tolerance of grape buds and the synthesis of these sugars can be enhanced by ABA treatment. This study also found that ABA application can promote raffinose accumulation, however, this sugar may play a more important role in the early acclimation stage. The preliminary results suggest that raffinose accumulated first in buds, then its decrease in mid-winter corresponded with the increase of smaller sugars, such as sucrose, fructose, and glucose, which in turn, corresponded with reaching maximum freezing tolerance. It is concluded that ABA is a cultural practice tool that can be used to enhance freezing tolerance of grapevines.